SPORTS ENDOWMENT FUND: A PANACEA FOR PRESENT AND FUTURE DEVELOPMENT OF SPORTS IN NIGERIA - Bichi, Sani Muktar (FUDMA JOURNAL OF SCIENCES, 2023)
This paper discussed the way and manner government at various levels in Nigeria handled sports generally for participation and development. Issues such as funding of sports, objectives of sports endowment fund, source of fund for sports, ways and strategies for fund raising for sports were discussed. Conclusion andrecommendations were offered such as Government at all levels such as Federal, State and Local should exercise their responsibilities and functions as provided in the National Sports Development Policy.